Trends Of Elements Fe And Mn In Coal Mining Waste At Tenggarong District. Kutai Kartanegara East Kalimantan - Sujiman SUJIMAN; Sundek HARIYADI (Indonesia Strategic Sustainability, 2022)
This study aims to determine the condition of Fe and Mn waste and to determine the tendency of Fe and Mn elements in several settling ponds of coal mines in Kutai Kartanegara Regency, East Kalimantan. The trend of Fe waste in mine 1, from January to March 2020 showed an increase, where in March it was very high up to 6,454 mg/lt. Then it decreased again to 0.899 mg/lt in May, then rose slightly again until September. In mine 2, the trend of Fe concentration from January to March 2020 showed an increase, where in March it was very high up to 62.30 mg/lt. The trend of the concentration of elemental Fe in mining for nine months is still below the quality standard set by the government. Meanwhile in Mine 4, the Fe concentration tends to be high in February 2020. Meanwhile, for other months, the concentration is quite good.